2017
DOI: 10.5194/acp-2017-307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric mercury in the southern hemisphere tropics: seasonal and diurnal variations and influence of inter-hemispheric transport

Abstract: Mercury is a toxic element of serious concern for human and environmental health. Understanding its natural cycling in the environment is an important goal towards assessing its impacts and the effectiveness of mitigation strategies. Due to the unique chemical and physical properties of mercury, the atmosphere is the dominant transport pathway for this heavy metal, with the consequence that regions far removed from sources can be impacted. However, there exists a dearth of long-Term monitoring of atmospheric m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[25] for tropical regions. Howard et al [40] however observed vegetation and soil concentrations in a tropical grassland site of only 9 µg kg −1 , stating that these samples were taken in an area that had undergone burning within the previous months. Clearly further vegetation and soil sampling in these ecoregions can assist in constraining Australian biomass burning mercury emission estimates.…”
Section: Gem and Pbm Emission Ratiosmentioning
confidence: 98%
“…[25] for tropical regions. Howard et al [40] however observed vegetation and soil concentrations in a tropical grassland site of only 9 µg kg −1 , stating that these samples were taken in an area that had undergone burning within the previous months. Clearly further vegetation and soil sampling in these ecoregions can assist in constraining Australian biomass burning mercury emission estimates.…”
Section: Gem and Pbm Emission Ratiosmentioning
confidence: 98%